Heat transfer enhancement using nanofluids in the automotive cooling system - Adnan Mohammed, Hussein (2014)
The automotive cooling system is a significant part of the car that removes the engine generated heat outside across the radiator. The increasing demand of nanofluids for industrial applications has led many researchers to focus on the subject in the last decade. The limited thermophysical properties and heat transfer fo liquids across the car radiator have resulted in much research to find better coolant fluids. Space constraints are another key issue in the evofofotua applications to remove heat from high heat flux generating surfaces of automobile engines. In order to improve thermophysical properties of the coolant fluid to enhance heat transfer in the automotive cooling system, nanofluids have been utilized as a coolant. This study aims to enhance heat transfer with a slight pressure drop in the automotive cooling system by using multi types of nanoparticles dispersed in various types of basefluids. The appropriate type of nanofluids and the influence of different nanofluids on the heat transfer performance for the car cooling system have been identified. The radiator performance efficiency to reduce the radiator size and weight has been studied. The friction factor and heat transfer enhancement using different types of nanofluids are studied. The TiO2 and SiO2 nanopowders suspended in four different base fluids (pure water, EG, 10%EG+90%W and 20%EG+80%W) are prepared experimentally. The thermophysical properties of both nanofluids and base fluids have been measured and validated with the standard and the experimental data available. The experimental test rig setup included a car radiator, collecting tank, pump, rotameter, valves and plastic tubes. The evaluation of the friction factor and heat transfer coefficient by taking readings of the temperature and pressure drop under laminar flow condition were conducted. The volume flowrate was found to be in the range of (1-5LPM) for pure water and (3-12LPM) for other base fluids; while, the inlet temperature and nanofluid volume fraction were in the range of (60-80oC) and (1- 4%) respectively. The CFD analysis for the nanofluids flow inside the flat tube of a car radiator under laminar flow was carried out. A simulation study was conducted by using the finite volume oaotfm to solve the continuity, momentum, and energy equations. The geometry meshing of problem with a description of the boundary conditions was performed by using commercial software to determine the friction factor and heat transfer coefficient. The experimental results showed the friction factor decreased with the increase of the volume flowrate and increased with the increase of nanofluid volume fraction but slightly decreased with the increase of the inlet temperature. The simulation results showed good agreement with the experimental data with deviation not exceeding 4%. The experimental results showed the heat transfer coefficient increased with the increase of the volume flowrate, the nanofluid volume fraction and the inlet temperature. The simulation results showed good agreement with the experimental data with deviation not exceeding 6%. In addition, the SiO2 nanofluid showed higher values of the friction factor and heat transfer coefficient than TiO2 nanofluid. The base fluid (20%EG+80%W) gave higher values of the heat transfer coefficient and proper values of friction factor compared to other base fluids. The 4% of SiO2 nanoparticles suspended in (20%EG+80%W) base fluid was significant augmentation of heat transfer in the automobile radiator. The regression equations among input (Reynolds number, Prandtl number, and nanofluid volume fraction) and response (friction factor and Nusselt number) were found to be correlated. The experimental results were compared with the experimental data available and there were good agreements with a maximum deviation of approximately 5%